EFEITO DO TREINAMENTO DE FORÇA SOBRE A QUALIDADE DE VIDA EM IDOSAS - Mariano, Eder Rodrigo (2012)
Muscle strength is an important variable during aging to be associated with the functional capacity of the human musculoskeletal system, particularly the elderly. The loss of motor units (sarcopenia) and the decline in the ability of neural recruitment of such units (dinapenia) occur after the fifth decade of life, are increasing after age 60 and worsen with the years. The decrease in the quality of muscle contraction may undermine the autonomy and independence of the elderly, making it difficult to perform activities of daily living and may have a negative effect on their quality of life. This study aimed to investigate the effects of strength training on muscle strength and quality of life in elderly women. To this end, we used the dynamometer N2000PRO and Quality of Life Questionnaire - Short (SF-36). The study included 36 volunteers, aged from 60 years, divided into: sedentary group (GS = 16), consisting of elderly who do not perform any kind of resistance exercise and training group (TG = 20) composed of elderly women were subjected to strength training program lasting 60 minutes each session, twice a week for 12 weeks. The training consisted of the following exercises: squats, knee extension, knee flexion, seated row low, upright row, development, arm lateral raise, biceps curl and triceps with dumbbell. The training intensity was determined based on the area of maximum repetitions (8-12 reps) and the order of execution of the exercises. It was observed after resistance training, a statistically significant increase in strength of knee extensors (p = 0.0032) and extensors of the lumbar spine (p = 0.0207). In the assessment of quality of life were noted statistically significant improvements in functional capacity (p = 0.0092), the general health status (p = 0.0075), vitality (p = 0.0015) and mental health (p = 0.0154). We conclude that the training was effective in increasing the strength of the knee extensors and lumbar spine, and improve the quality of life in mainly on the functional capacity of the elderly investigated.